FAKTOR RISIKO KEJADIAN BERAT BADAN LAHIR RENDAH DI AREA PERTANIAN (STUDI DI KABUPATEN BREBES) - Ratnasari, Diah; Suhartono, Suhartono; Rahfiludin, Mohammad Zen (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
The aim of this study was to analyze the risk factors of Low Birth Weight (LBW) in agricultural area (Breses district) with high pesticide exposure. The research was an observational study with case control design. Study subject were post partum-productive age (20-35 years) women, consisting of 60 cases (LBW) and 60 controls (non-LBW). The independent variables were maternal weight gain during pregnancy, MUAC in early pregnancy, hemoglobin levels in the third trimester body mass index before pregancy and level of pesticides exposure. Nutrient intake data was obtained by semiquantitative food frequency questionnaires (FFQ), maternal and child health (KIA) book and data on level of pesticide exposure was obtained through a structured interview. Data were analyzed by calculating the Odds Ratio (OR) using logistic regression. There was no differences in age between cases and controls. Median length, mother’s education level, BMI and MUAC among the cases was lower than the control group. Low protein adequacy level (OR= 8.9; 95%CI:1.6-227.7); less weight gain (OR=9.1; 95%CI:2.9-28,); High pesticides exposure (OR=7.4; 95%CI:1.3-40.9); low MUAC <23.5 cm (OR=4.6; 95%CI:1.3-15.5) were LBW risk factors in Brebes. Inadequacy of nutritients and high pesticides exposure during pregnancy was LBW risk factors. Women are advised to increase nutrients intake and avoid pesticides exposure during pregnant.